2012
DOI: 10.1530/rep-11-0350
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide and mitochondrial function in aging oocytes: joggling a new hypothesis and old players

Abstract: Maternal aging adversely affects oocyte quality (function and developmental potential) and consequently lowers pregnancy rates while increasing spontaneous abortions. Substantial evidence, especially from egg donation studies, implicates the decreased quality of an aging oocyte as a major factor in the etiology of female infertility. Nevertheless, the cellular and molecular mechanisms responsible for the decreased oocyte quality with advanced maternal aging are not fully characterized. Herein we present inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 99 publications
0
17
0
1
Order By: Relevance
“…More recently, Yamamoto et al [42] demonstrated the secretion of placental lactogen (elPL) by elephant trophoblast tissue and speculated that this chorionic hormone may be the essential luteotrophic stimulus for the enlargement of the fetal gonads and their synthesis of progestagens to assist the accessory corpora lutea in the maternal ovaries to maintain the pregnancy state. The highly vascularised nature of the fetal ovary from 18 months of gestation to term would help to transport the progestagens being synthesized by the interstitial tissue to the fetal, and hence to the maternal circulation to boost the supply of progestagens for pregnancy maintenance [43]. …”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yamamoto et al [42] demonstrated the secretion of placental lactogen (elPL) by elephant trophoblast tissue and speculated that this chorionic hormone may be the essential luteotrophic stimulus for the enlargement of the fetal gonads and their synthesis of progestagens to assist the accessory corpora lutea in the maternal ovaries to maintain the pregnancy state. The highly vascularised nature of the fetal ovary from 18 months of gestation to term would help to transport the progestagens being synthesized by the interstitial tissue to the fetal, and hence to the maternal circulation to boost the supply of progestagens for pregnancy maintenance [43]. …”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for cumulus cell-associated acceleration of post-ovulatory ageing has been detailed in publications by Perez et al (2005) and Kujjo & Perez (2012). These researchers propose that the bioactive sphingolipid, ceramide, generated by the cumulus cells may be responsible for mitochondrial dysfunction and subsequent ageing and apoptosis in post-ovulatory oocytes.…”
Section: Cumulus Cellsmentioning
confidence: 99%
“…Furthermore, ceramide has been shown to be involved in the mechanism of oocyte aging in a mitochondria-dependent mechanism. More specifically during aging, mitochondrial ceramide levels decrease and consequently alter the mitochondrial structure and function contributing to reduced oocyte quality [56]. Alternatively, short exposure to exogenous C8-ceramide was shown to strongly increase mitochondrial prohibitin (PHB) expression, maintaining mitochondrial integrity, and protecting germ cells.…”
Section: Ceramide and Cellular Signalingmentioning
confidence: 99%